Influence of a Commercial Fuel Additive on Combustion Characteristics - Ali, Md Isa (2001)
The worse quality fuels in over 30 years have contributed to exessive emissions, poor performance and many others. Today, there exists a variety of fuel additives to perform under severe conditions to improve the fuel's combustion characteristics. However, the effectiveness and mode of operation of such additives are not completely understood. This study discussed the experimental findings using a Combustion Laboratory Unit. Experiments were performed to determine the effects of a particular fuel additive on combustion characteristics which includes emissions, efficiency, heat release and the fuel consumption rate. Fuels (gasoline) with and without the additive were fired succesively in the unit. MARVEL, a commercial fuel additive was used for the analysis. The concentration of the additive in the basic fuel were within 0.2% to 1.6% by volume. It was found that, with the presence of the fuel additive, it decreased the carbon dioxide emission by 2%, maintained the carbon monoxide level less than 4% and the heat release increased by 5%. The additive was also found to increase the combustion efficiency by 8% and decreased the fuel consumption rate by 5%. From the above findings. the use of the additive to modify certain combustion characteristics of fuel can improve the basic fuel quality and performance. As this additive has been developed primarily for gasoline fuels. many such additives can also be employed in other type of fuel.